Localized Plumes Drive Front‐Wide Ocean Melting of A Greenlandic Tidewater Glacier. Issue 22 (27th November 2018) - Slater, D. A.; Straneo, F.; Das, S. B.; Richards, C. G.; Wagner, T. J. W.; Nienow, P. W.
Abstract: Recent acceleration of Greenland's ocean‐terminating glaciers has substantially amplified the ice sheet's contribution to global sea level. Increased oceanic melting of these tidewater glaciers is widely cited as the likely trigger, and is thought to be highest within vigorous plumes driven by freshwater drainage from beneath glaciers. Yet melting of the larger part of calving fronts outside of plumes remains largely unstudied. Here we combine ocean observations collected within 100 m of a tidewater glacier with a numerical model to show that unlike previously assumed, plumes drive an energetic fjord‐wide circulation which enhances melting along the entire calving front. Compared to estimates of melting within plumes alone, this fjord‐wide circulation effectively doubles the glacier‐wide melt rate, and through shaping the calving front has a potential dynamic impact on calving. Our results suggest that melting driven by fjord‐scale circulation should be considered in process‐based projections of Greenland's sea level contribution. Plain Language Summary: As the world warms, loss of ice from the Greenland Ice Sheet will be a significant source of sea level rise. Greenland loses ice partly through the flow of huge rivers of ice called tidewater glaciers that dump solid ice directly into the ocean. Over the past two decades, tidewater glaciers around Greenland have accelerated dramatically, increasing Greenland's contribution to global mean sea level. There is mounting evidence that these accelerations have been driven by ocean warming, and a resulting increase in the rate at which the ocean melts the front of tidewater glaciers (called submarine melting). Yet submarine melting is at present poorly understood, in part due to the danger and difficulty of collecting data close to tidewater glaciers. We present observations of the ocean in front of a tidewater glacier that are unprecedented in their proximity to the glacier. These data reveal an ocean circulation which flushes warm water along the front of the glacier, driving high rates of submarine melting. We then use a numerical model to identify what drives this circulation. Our results are an important step toward understanding a key process which will modulate future sea level contribution from the Greenland ice sheet. Key Points: Ocean observations that are unprecedented in their spatial detail and proximity to a Greenlandic tidewater glacier are reported Despite being highly localized, plumes drive fjord‐wide circulation and hence glacier‐wide submarine melting at tidewater glaciers Fjord‐scale submarine melting drives significant mass loss and may promote calving, hence is a key process determining glacier stability